Biochemical, cellular and structural characterization of novel and selective ERK3 inhibitors. Issue 22 (15th November 2020) - Grädler, Ulrich; Busch, Michael; Leuthner, Birgitta; Raba, Michael; Burgdorf, Lars; Lehmann, Martin; Linde, Nina; Esdar, Christina
Graphical abstract: Highlights: Triazolo[4, 5- d ]pyrimidin-5-amines were identified as novel ERK3 inhibitors with sub-100 nanomolar biochemical potencies. Highly potent inhibitors such as 18 revealed an attractive kinase selectivity profile. ERK3 crystal structures clarified inhibitor binding in ATP site with potential conformational impact on MK5 recognition. Inhibitors were also highly potent in a cellular ERK3 NanoBRET assay with excellent correlation to the biochemical assay. Abstract: Triazolo[4, 5- d ]pyrimidin-5-amines were identified from kinase selectivity screening as novel ERK3 inhibitors with sub-100 nanomolar potencies in a biochemical assay using MK5 as substrate and with an attractive kinase selectivity profile. ERK3 crystal structures clarified the inhibitor binding mode in the ATP pocket with impact on A-loop, GC-loop and αC-helix conformations suggesting a potential structural link towards MK5 interaction via the FHIEDE motif. The inhibitors also showed sub-100 nM potencies in a cellular ERK3 NanoBRET assay and with excellent correlation to the biochemical IC50 s. This novel series provides valuable tool compounds to further investigate the biological function and activation mechanism of ERK3.